Azimuthal Anisotropy of Different Quark-flavored Particles in High Energy "simulated" Proton-Proton Collisions - Rateb, Mahmoud (AUC Knowledge Fountain, 2023)
Anisotropic flow in high energy heavy-ion collisions is taken as a key evidence for the formation of QGP for brief seconds right after the collisions. Hydrodynamic models including QGP formation are accurate at predicting the azimuthal anisotropy of the produced particles at low transverse momenta. At high momenta however, hydrodynamic models predict no azimuthal anisotropy for particles of different masses and quark-flavors; the logic being that because of their high momenta, the particles pass through the media without having any time to have any reactivity. This is contrary to results from experiments where measurements of particles of different quark flavors show non-zero elliptic flow. To study this deviation, we run PYTHIA simulation of proton-proton collisions at center- of-mass energies equivalent to those at RHIC and LHC; 200 GeV and 13 TeV. Since in PYTHIA simulations no QGP if formed, and there is no final-state interaction, results in our simulation would act as probes to be compared to the results of elliptic flow from real experiments. Our results showed non-zero results for the elliptic flow of pions, heavy mesons and direct photons. Those results are evident of the possible bias in the way the reaction plane is calculated, since all the other factors are controlled for in the PYTHIA simulations. To make up for this inherent bias, the results from PYTHIA should be subtracted from the results of elliptic flow in real experiments, to end up with unbiased results for elliptic flow from the different colliders.